2014
DOI: 10.1109/tcbb.2014.2309592
|View full text |Cite
|
Sign up to set email alerts
|

Distance-Based Phylogenetic Methods Around a Polytomy

Abstract: Abstract. Distance-based phylogenetic algorithms attempt to solve the NP-hard least squares phylogeny problem by mapping an arbitrary dissimilarity map representing biological data to a tree metric. The set of all dissimilarity maps is a Euclidean space properly containing the space of all tree metrics as a polyhedral fan. Outputs of distancebased tree reconstruction algorithms such as UPGMA and Neighbor-Joining are points in the maximal cones in the fan. Tree metrics with polytomies lie at the intersections o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Eickmeyer et al [106] developed the geometric view of the BME and NJ methods and defined BME polytopes in order to compare the accuracy of the NJ method with the BME method. Similarly, Davidson and Sullivant [107] used the polyhedral subdivisions to compare the accuracy of the NJ, UPGMA (Unweighted Pair-Group Method with Arithmetic Mean) and Least Squares methods. Here we propose to extend this approach to cophylogenies, namely to joint BME polytopes.…”
Section: Methodological Questionsmentioning
confidence: 99%
“…Eickmeyer et al [106] developed the geometric view of the BME and NJ methods and defined BME polytopes in order to compare the accuracy of the NJ method with the BME method. Similarly, Davidson and Sullivant [107] used the polyhedral subdivisions to compare the accuracy of the NJ, UPGMA (Unweighted Pair-Group Method with Arithmetic Mean) and Least Squares methods. Here we propose to extend this approach to cophylogenies, namely to joint BME polytopes.…”
Section: Methodological Questionsmentioning
confidence: 99%
“…Example 3.3. Figure 5 depicts three ultrametrics in the set of closest ultrametrics to δ = (2,4,6,8,10,12). The subdominant ultrametric is δ U = (2, 4, 6, 4, 6, 6), d(δ, U 4 ) = 3, and the canonical closest ultrametric (pictured far left) is δ c = (5,7,9,7,9,9).…”
Section: Rooted Trees and Ultrametricsmentioning
confidence: 99%
“…The idea behind most of these proofs is to find a linear space that contains the ultrametrics for many different tree topologies and apply the constructions for linear spaces developed in Section 2. In [6], the authors study the geometry of the set of dissimilarity maps around a polytomy with respect to the Euclidean norm. They showed that locally this space could be partitioned according to the closest tree topology.…”
Section: Rooted Trees and Ultrametricsmentioning
confidence: 99%
See 2 more Smart Citations